The Role of Electrical Stimulation in Management of Retinal and Optic Nerve Degenerative and Dystrophic Disorders. Literature Review - L. S. Pateyuk; A. K. Drakon; V. M. Sheludchenko; N. B. Korchazhkina (Oftalʹmologiâ, 2021)
This article presents actual data on the retinal and optic nerve electrical stimulation. The physical basics of the electrical stimulation biological effect on cellular elements and nerve fibers are discussed. Ocular indications for electrical stimulation, as well as local and general contraindications are listed. Strategies of delivery and brief historical overview are given. The article presents current data on the electrical stimulation clinical effectiveness in the management of patients with degenerative and dystrophic diseases of the retina and optic nerve: age-related macular degeneration, retinitis pigmentosa, optic nerve atrophy and glaucoma optic neuropathy. The data on the clinical efficacy of electrophthalmostimulation in the treatment of patients with degenerative-dystrophic diseases of the retina and optic nerve: age-related macular degeneration, retinal pigment abiotrophy, optic nerve atrophy and glaucoma optic neuropathy are presented. Electrophthalmostimulation is a modern method of physical treatment of patients with diseases of the retina and optic nerve of a degenerative-dystrophic nature. The method is generally recognized and widely used in clinical work, not only traditionally on the territory of the Russian Federation, but also in world practice. In experiments and on animal models, the indisputable advantage of electrical stimulation of the retina and optic nerve has been proven — the etiopathogenetically determined preservation of the remaining and restoration of lost visual functions in case of ophthalmic diseases leading to blindness. Further development of this direction of electrotherapy includes standardization of the most effective techniques for various ophthalmopathologies and optimization of the parameters of courses and sessions of electrical stimulation of the retina and optic nerve. The latter presupposes the conduct of multicenter, randomized, placebo-controlled clinical trials with a sufficient volume of clinical material and reliable statistical processing of the results obtained.